Advanced strategy guide to Minecraft - O'Brien, Stephen J., 1969- (Que Publishing, 2016)
The Advanced Strategy Guide to Minecraft Make Minecraft whatever YOU want it to be! After you've learned to survive in Minecraft, the fun really begins . Minecraft's advanced features support stunning creativity--and that's still just the beginning. More than ever, Minecraft 1.9 can be whatever you and millions of other players dream up! Custom-crafted adventure maps... new trading systems and societies... incredible mods that take Minecraft into the far future... Minecraft's potential is simply astounding. This full-color guide brings together all of today's most amazing Minecraft resources and techniques. Why struggle with outdated web tutorials or bewildering YouTube videos? Mega-bestselling author Stephen O'Brien will show you how to get it all, and do it all ! Create and manage unique Minecraft 1.9 configurations with their own versions, worlds, resource packs, and profiles Automatically mass-produce sugar cane, melons, wheat, and more Supercharge mining operations to excavate infinite amounts of obsidian Take control of the mayhem with mob farms: mass-produce your own zombies, spiders, creepers, and skeletons Craft amazing armor, weapons, and tools Build in any style that inspires you: medieval, Victorian, Viking, Japanese, modern, suburban, you name it Create natural-looking terrain and trees, decorate with 2D pixel art, and build 3D statues Construct smarter, more efficient power and transportation systems Assemble amazing redstone circuitry with Monostable and Redpower 2 Generate massive resources with gigantic oil refineries and quarries Create and share exciting adventure maps and learn the secrets of CommandBlocks Export your greatest adventures to YouTube, Vimeo, or HD video Stephen O'Brien is author of the mega-bestselling The Ultimate Player's Guide to Minecraft as well as many other books. An Australian-born writer and entrepreneur now residing in Sydney after too many years in Silicon Valley, his 30 books include several bestsellers. He founded Typefi, the world's leading automated publishing system, and invented the award-winning mypressi portable espresso maker. He's a perpetual innovator who remains astounded at the unparalleled creativity Minecraft can engender. Minecraft is a trademark of Mojang Synergies / Notch Development AB. This book is not affiliated with or sponsored by Mojang Synergies / Notch Development AB. Register your book at quepublishing.com/register and save 35% off your next purchase!